2023
DOI: 10.1002/ijc.34493
|View full text |Cite
|
Sign up to set email alerts
|

Pain in desmoid‐type fibromatosis: Prevalence, determinants and prognosis value

Abstract: The aim of this study is to evaluate the prevalence, determinants and prognostic value of pain at diagnosis in patients with desmoid‐type fibromatosis (DF). We selected patients from the ALTITUDES cohort (NCT02867033), managed by surgery, active surveillance or systemic treatments, with pain assessment at diagnosis. Patients were invited to fill QLQ‐C30 questionnaire and Hospital Anxiety Depression Scale. Determinants were identified using logistic models. Prognostic value on event‐free survival (EFS) was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Pain is a common symptom of desmoid tumor and is often related to the size and location of the tumor. Studies have shown that one-third of confirmed desmoid tumor patients experience pain, particularly those with tumors larger than 5 cm or located in the neck or shoulder region (7). In these current cases, neither patient felt significant pain, probably because the affected area was non-invasively located in the mesentery.…”
Section: Clinical Manifestationmentioning
confidence: 52%
“…Pain is a common symptom of desmoid tumor and is often related to the size and location of the tumor. Studies have shown that one-third of confirmed desmoid tumor patients experience pain, particularly those with tumors larger than 5 cm or located in the neck or shoulder region (7). In these current cases, neither patient felt significant pain, probably because the affected area was non-invasively located in the mesentery.…”
Section: Clinical Manifestationmentioning
confidence: 52%
“…The presence of pain was associated with lower performance status ( P = 0.024) and functional impairment ( P = 0.001). The 3-year event-free survival probability in the absence of baseline pain was 72.2% (95% CI, 65.1–78.1) and in the presence of baseline pain 53.9% (95% CI, 43.3–63.4) [ 43 ]. In a phase 3 trial of an investigational agent, nirogacestat (DeFi trial, n = 142), 41% of patients with progressing DT had uncontrolled pain at baseline, defined as average worst pain intensity score of > 4 as measured using the Brief Pain Inventory-Short Form (range 0–10, with higher scores indicating worse pain) [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a phase 3 trial of an investigational agent, nirogacestat (DeFi trial, n = 142), 41% of patients with progressing DT had uncontrolled pain at baseline, defined as average worst pain intensity score of > 4 as measured using the Brief Pain Inventory-Short Form (range 0–10, with higher scores indicating worse pain) [ 44 ]. The pain severity and associated burden of disease can lead to anxiety and depression in many patients [ 4 , 43 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are rare cases reported of desmoid tumors in extra-abdominal sites such as the vulva, larynx, neck, and popliteal fossa [ 13 , 14 ]. Furthermore, a recent study involving 382 patients with desmoid-type fibromatosis found that the prevalence of pain was only 36%, thereby highlighting the relatively uncommon nature of this symptom in the condition [ 15 ].…”
Section: Discussionmentioning
confidence: 99%